Comparative evaluation of mastoid pneumatization pattern using X-ray mastoid and high-resolution computed tomography temporal bone in unilateral squamosal chronic otitis media - Dhiman, Akanksha; Gupta, Ankur; Sharma, Nishi; Prasad, Akhilandeswari (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Chronic otitis media (COM) affects 0.5-30% of individuals in any community and over 20 million people are estimated to suffer from this condition worldwide. COM often evolves in a continuum. Squamosal disease is more commonly found in poorly pneumatized bones, but whether the sclerosis is relevant to the etiology of the disease or is caused by it, has not been fully resolved. Our study aimed at comparing the mastoid pneumatization patterns obtained using X-ray mastoid and high-resolution computed tomography (HRCT) temporal bone. It was an interventional study. Methods: Sixty patients of unilateral squamosal COM, aged more than 8 years, underwent X-ray mastoid Schuller’s view and HRCT temporal bone, using Philips extended brilliance 48 slice CT. Results: Upon analysis, in diseased and healthy ears, the coincidence of X-ray and HRCT findings was 63.33% and 80% respectively. Conclusions: HRCT temporal bone should be done in all cases of squamosal COM to know the extent of the disease, pneumatization patterns and the presence of anatomical variations.